2018
DOI: 10.12973/iji.2018.1125a
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Academic Dishonesty Scale (ADS): Presenting a Multidimensional Scale

Abstract: The purpose of the study was to develop a scale measuring academic dishonesty of undergraduate students. The sample of the study constitutes nine hundred undergraduate students selected via random sampling technique. After receiving expert's opinions for the face and content validity of the scale, the exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were applied. EFA favored a six factor structure viz: cheating in examination; plagiarism; outside help; prior cheating; falsification and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 57 publications
(65 reference statements)
0
24
0
3
Order By: Relevance
“…At the level of dishonest behavior recognition, in the early days, researchers mostly used students' self-reporting methods for research. For example, Bashir et al (2018) developed a scale that is suitable for detecting various types of learning dishonesty [17]. Peer et al (2014) have found that students' reluctance to admit cheating means that self-reporting often underestimates academic dishonesty [18].…”
Section: Rq3: What Are the Methods To Identify College Students' Learmentioning
confidence: 99%
“…At the level of dishonest behavior recognition, in the early days, researchers mostly used students' self-reporting methods for research. For example, Bashir et al (2018) developed a scale that is suitable for detecting various types of learning dishonesty [17]. Peer et al (2014) have found that students' reluctance to admit cheating means that self-reporting often underestimates academic dishonesty [18].…”
Section: Rq3: What Are the Methods To Identify College Students' Learmentioning
confidence: 99%
“…Logical validation was carried out by several experts related to the field then the validation results were analyzed using V-Aiken. Logical validation was analyzed using product moment correlation (Bashir & Bala, 2018;Sadhu & Laksono, 2018). Data obtained from the results of the study were then subjected to the analysis prerequisite test, namely the normality and homogeneity tests (Aiken, 1985;Mardapi, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Three forms of academic dishonesty in general, namely (1) giving, speaking and receiving information, (2) using prohibited materials, (3) utilizing people's weaknesses, procedures or processes to gain academic benefits [25]. Bashir and Bala who developed an instrument of academic dishonesty scale suggested that the characteristics of academic dishonesty were cheating / cheating during exams, plagiarism, asking for help from others, working with friends to cheat, falsify and lie in complementing assignments [26].…”
Section: Forms Of Academic Dishonestymentioning
confidence: 99%
“…The instrument for measuring dishonesty was adapted from Hilal Bashir and Ranjan Bala who developed the Academic Dishonesty Scale (ADS) measurement tool. The ADS instrument has a high internal consistency value α = 0.831 [26]. The ADS instrument was translated to Indonesian for ease of getting response.…”
Section: Instrumentationmentioning
confidence: 99%